English Literature Students’ Attitude to AI-Powered Tools - Amirudin Amirudin; Tutik Ratna Ningtyas; Bambang Irawan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
AI-powered tools have been widely used in many fields, including education. The use of AI is prevalent due to its convenience offered to its users. Students in this era are among those who make use of this technology. The use can vary depending on the needs and intentions the students have. Therefore, it is necessary to find out how the students view this technology. This research aims at exploring how students see AI as beneficial tools for them as well as how students AI might cause concerns among them. This research applies a qualitative exploratory approach to collect the data. The findings show that students feel benefited from the use of AI during their learning journey including the instrumental functions and the more advanced functions of AI. On the other hand, the findings also show how students feel concerned about AI despite their regular use. The students realize that AI use may lead to overdependence causing the decline of critical thought. All in all, the use of AI must be accompanied by ethical considerations so that AI will not replace the cognitive process of its users.